High non-compliance rate with anti-tuberculosis treatment: a need to shift facility-based directly observed therapy short course (DOTS) to community mobile outreach team supervision in Saudi Arabia - Abdullah Jaber AlSahafi; Hassan Bin Usman Shah; Mashal Mesfer AlSayali; Najlaa Mandoura; Mohammed Assiri; Emad Lafi Almohammadi; Alaa Khalawi; Abdullah AlGarni; Maimona Kamal Filemban; Adel Khaled AlOtaibe; Abdulaziz W. A. AlFaifi; Fatima AlGarni (BMC, 2019)
Abstract Background Tuberculosis (TB) remains a major global public health problem in many developing countries including Kingdom of Saudi Arabia (KSA). Patient compliance with anti-tuberculosis treatment is a determining factor in controlling the spread of TB. This study compares the default rate and the perception of their treatment among TB patients being treated by means of a community mobile outreach approach, with those of patients being treated by means of a facility-based Directly Observed Treatment Short course (DOTS) in the Jeddah region of Saudi Arabia. Methods A comparative cross-sectional study of 200 TB patients who presented at the Madain Alfahd Primary Health Care Center (PHCC) Jeddah, between January 2018 and November 2018 was undertaken. In one group, randomly assigned patients were served by mobile outreach teams who administered oral anti-TB treatment under the DOTS regime. In the other group, the patients were treated by means of the traditional facility-based DOTS treatment. A questionnaire measuring patient attitudes and understanding of the disease and their treatment modes was completed by patients at the beginning of their treatment, and again after 3 months. The results were analysed by means of independent and Paired T Tests, along with chi square analysis. Results We found that the overall default rate among those patients served by our mobile outreach team was only 3%, compared with a 22% default rate among non-mobile team treated patients (p = < 0.001). A major change in the attitude and understanding scores of patients was noted in both groups after 3 months. A significant difference was also noted in the mean compliance scores (mobile team served =58.43 and facility-based =55.55, p < 0.001) after 3 months of treatment. Conclusion Our study indicated that treatment by means of our mobile outreach DOTS can offer an effective strategy for the treatment of TB patients. A reduced patient default rate and a better understanding of the disease and its treatment confirmed a positive impact of mobile outreach teams on these patients. Treating TB patients by means of mobile outreach teams can thus be recommended as a means for the cure and prevention of the further spread of the disease.